(untitled) (UNED Research Journal, 2021)
Introduction: In the mountain forests of the Córdoba, Argentina, foxes (Lycalopex gymnocercus) include in their diet fruits of exotic species such as blackberries (Morus nigra), an invasive species native of Asia. Objective: To learn if blackberry seeds suffer damage in the digestive tract of foxes, and if this affects the viability, germination power, onset and germination rate. Methods: Blackberry seeds were collected in the field and from fresh feces of captive foxes; 300 seeds were randomly selected per treatment and kept in a germinator at 25 ° C. The germination criterium was the emergence of the radicle. Results: All the seeds extracted from the feces were healthy. The onset of germination occurred on the same day in both treatments, even though germination rates were higher for the seeds extracted directly from the fruits. Conclusions: Despite minor damage to the seeds, the fox is a disperser of blackberry seeds.